2016
DOI: 10.1016/j.ab.2015.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Immunomagnetic capture and colorimetric detection of malarial biomarker Plasmodium falciparum lactate dehydrogenase

Abstract: We report a sensitive, magnetic bead-based colorimetric assay for Plasmodium falciparum lactate dehydrogenase (PfLDH) in which the biomarker is extracted from parasitized whole blood and purified based on antigen binding to antibody-functionalized magnetic particles. Antigen-bound particles are washed, and PfLDH activity is measured on-bead using an optimized colorimetric enzyme reaction (limit of detection [LOD] = 21.1 ± 0.4 parasites/μl). Enhanced analytical sensitivity is achieved by removal of PfLDH from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 12 publications
0
19
1
Order By: Relevance
“…Anti- p LDH and anti-HRP2 beads were prepared as reported previously. 19 , 24 Briefly, anti- p LDH (Vista 19g7) or anti-HRP2 (Abcam ab9203) was biotinylated with EZ-Link NHS–PEG4–Biotin, No-Weigh Format (Thermo no. 21329).…”
Section: Methodsmentioning
confidence: 99%
“…Anti- p LDH and anti-HRP2 beads were prepared as reported previously. 19 , 24 Briefly, anti- p LDH (Vista 19g7) or anti-HRP2 (Abcam ab9203) was biotinylated with EZ-Link NHS–PEG4–Biotin, No-Weigh Format (Thermo no. 21329).…”
Section: Methodsmentioning
confidence: 99%
“…For p LDH, magnetic microparticles were used to isolate Plasmodium falciparum lactate dehydrogenase ( Pf LDH) from lysed whole blood. The biomarker was then detected using the Malstat assay, and enzymatic turnover assay catalyzed by Pf LDH [15]. The detection limit for this method was 26 pM Pf LDH, an order of magnitude higher than the developed on-bead SCSD ELISA for p LDH and Pf HRPII.…”
Section: Resultsmentioning
confidence: 98%
“…Target-specific antibody-functionalized beads were prepared as reported previously [15]. Briefly, α- p LDH (Vista, 19g7) or α- Pf HRPII (Abcam, ab9203) antibodies were biotinylated with EZ-Link NHS-PEG4-Biotin, No-Weigh Format (Thermo Pierce #21329) in PBS with a 20× excess of NHS-PEG4 Biotin.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it is necessary to develop an alternative diagnostic biomarker instead of HRP2. In this study, we chose P. falciparum lactate dehydrogenase (PfLDH) as an alternative biomarker for the diagnosis of malaria (P. falciparum), which is a water-soluble enzyme that converts pyruvate to lactate in glycolysis in P. falciparum infection [5,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the limitations of existing diagnostics, several studies demonstrated improved detection efficiency by introducing nanoparticles such as magnetic beads. Markwalter et al successfully detected PfLDH up to 21.1 ± 0.4 parasites/ mL within 45 min using antibody-immobilized magnetic beads as a colorimetric assay [14]. Additionally, they developed a simultaneous capture and sequential detection of two malarial biomarkers (PfLDH and HRP2) on magnetic microparticles [23].…”
Section: Introductionmentioning
confidence: 99%